2016
DOI: 10.1007/s11738-016-2312-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phenolic compounds production in in vitro grown Rumex cyprius Murb.

Abstract: Plant tissue culture can readily be applied to the field of medicinal plants and secondary metabolites production. In this study, in vitro propagation protocol of Rumex cyprius Murb. was established. The highest shoot multiplication rate was observed from explants grown on MS medium supplemented with 1.5 mg/L BA (7.8 shoots per explant). For rooting, the maximum root induction rate was observed on MS medium supplemented with 1.5 mg/L IBA or 1.0 mg/L NAA. The longest roots were observed for plants grown on MS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The highest number of shoots per explant (12.6) was induced by 2mg L −1 BAP and it was associated with high percentage of shoot induction (70%). Our results support those found by Al Khateeb et al (2017), who reported that BAP induced the best results in shoot multiplication from shoot apex of R. cyprius when compared with TDZ and KIN. In contrast, Polygonum hydropiper exhibited a preferential multiple shoot induction from shoot tip on KIN over BAP (Hasan & Sikdar, 2010).…”
Section: Shoot Proliferation and Multiplicationsupporting
confidence: 92%
See 4 more Smart Citations
“…The highest number of shoots per explant (12.6) was induced by 2mg L −1 BAP and it was associated with high percentage of shoot induction (70%). Our results support those found by Al Khateeb et al (2017), who reported that BAP induced the best results in shoot multiplication from shoot apex of R. cyprius when compared with TDZ and KIN. In contrast, Polygonum hydropiper exhibited a preferential multiple shoot induction from shoot tip on KIN over BAP (Hasan & Sikdar, 2010).…”
Section: Shoot Proliferation and Multiplicationsupporting
confidence: 92%
“…However, IAA induced no roots from R. pictus shoots, even when applied with half-strength MS media ( Table 2), indicating that root induction may be influenced also by the suitability of the exogenously added growth regulator. The superiority of IBA as effective auxin for inducing in vitro rooting over IAA and NAA was previously pointed out (Moharami et al, 2014;Swain et al, 2016 andAl Khateeb et al, 2017). IBA was reported to be the most successful auxin in root formation in several plant species (Thomas, 2007;Shekhawat et al, 2015 andDewir et al, 2016), however an increase of IBA level (up to 2mg L −1 ) decreased the percentage of root induction, root number and root length of R. pictus (Table 2).…”
Section: In Vitro Root Formation and Acclimatizationmentioning
confidence: 74%
See 3 more Smart Citations